Health-promoting behaviors and related factors among high school teachers in the city of Rasht, Iran - Ebrahimzadeh, Shohreh; Sahebalzamani, Mohammad; Farahani, Hojjatollah; Adhami Moghadam, Farhad (Social Determinants of Health, 2017)
Background: Health Promoting Behaviors (HPB) are of great importance because of their potential benefits to prevent the progression of chronic diseases, reduce disease burden, improve quality of life, and reduce healthcare costs. The present study aimed to determine and compare HPB and related factors among high school teachers. Methods: A cross-sectional study was conducted on 257 high school teachers (138 women and 119 men) having at least associate degree in Rasht city, Iran during 2015. Data collection tool was a researcher-made questionnaire including the personal, familial, and social factors and Health-Promoting Lifestyle Profile (HPLPII) standard questionnaire. Data were analyzed using IBM SPSS Statistics for Windows, Version 24.0. running descriptive and inferential statistics, including independent sample t-test, analysis of variance. P values less than 0.05 were considered as statistically significant. Results: Among the participants 138 (53.7%) were female. The overall mean (SD) score of HPB among participants was 129.6 (22.64) and was undesirable. This score was significantly better among the women 130.6 (24.61) compared with men 128.5 (20.54) (P=0.01). The highest mean score of HPB was related to nutrition 26.8 (5.01), followed, respectively, by spiritual growth 22.6 (4.25) and interpersonal relations 21.7 (4.82). Physical activity with the mean (SD) score of 18.09 (4.14) had the lowest overall mean score of HPB. Female teachers had a significantly higher scores than men in all aspects (P<0.05), except for physical activity and stress management. Conclusion: The overall mean score of HPB among participants was undesirable. Total HPB in female teachers were better than that in the male teachers. Female teachers had a better status than men in all aspects except for physical activity and stress management.